Macroeconomic factors affecting the growth rate of FDI of AEC member countries using panel quantile regression - Tungtrakul T. (2017)
© Springer International Publishing Switzerland 2016. Macroeconomic factors affecting the growth rate of foreign direct investment (FDI) in AEC member countries were investigated using panel quantile regression to investigate the effects of foreign direct investment (FDI) of ASEAN Economic Community (AEC) member countries. Yearly data covering the period of 2001 to 2012 for nine countries except Myanmar were used for the estimation. As the data of Myanmar are limited, this study covered only Singapore, Philippines, Brunei, Cambodia, Indonesia, Laos, Malaysia, Vietnam and Thailand. The independent variables include the growth rate of gross domestic product, the growth rate of exchange rate ratio and inflation. The findings of this study show that the growth rate of gross domestic product affects the growth rate of foreign direct investment (FDI) positively and statistically significant at all levels of quantile except the quantile at 0.75.